QT spatial dispersion and sudden cardiac death in hypertrophic cardiomyopathy: Time for reappraisal. Issue 4 (October 2017) - Magrì, Damiano; Santolamazza, Caterina; Limite, Luca; Mastromarino, Vittoria; Casenghi, Matteo; Orlando, Paola; Pagannone, Erika; Musumeci, Maria Beatrice; Maruotti, Antonello; Ricotta, Agnese; Oliviero, Giada; Piccirillo, Gianfranco; et al.
Abstract: Background: The 12-lead surface electrocardiographic (ECG) analysis is able to provide independent predictors of prognosis in several cardiovascular settings, including hypertrophic cardiomyopathy (HCM). The present single-center study investigated the possible ability of several ECG-derived variables in stratifying sudden cardiac death (SCD) risk and, possibly, in improving the accuracy of the 2014 European Society of Cardiology guidelines. Methods: A total of 221 consecutive HCM outpatients were recruited and prospectively followed. All of them underwent a full clinical and instrumental examination, including a 12-lead surface ECG to calculate the dispersion for the following intervals: QRS, Q-Tend (QT), Q-Tpeak (QTp), Tpeak-Tend (TpTe), J-Tpeak (JTp), and J-Tend (JT). The study composite end-point was SCD, aborted SCD, and appropriate implantable cardioverter defibrillator (ICD) interventions. Results: During a median follow-up of 4.4 years (25th–75th interquartile range: 2.4–9.4 years), 23 patients reached the end-point at 5-years (3 SCD, 3 aborted SCD, 17 appropriate ICD interventions). At multivariate analysis, the spatial QT dispersion corrected according to Bazett's formula (QTcd) remains independently associated to the study endpoint over the HCM Risk-SCD score (C-index 0.737). A QTcd cut-off value of 93 ms showed the best accuracy in predicting the SCD endpoint within the entire HCM study cohort (sensitivity 56%, specificity 75%, positive predictive value 22%, negative predictive value 97%). Conclusion: Our data suggest that the QTcd might be helpful in SCD risk stratification, particularly in those HCM categories classified at low-intermediate SCD risk according to the contemporary guidelines.